Infant Anemia - Dávila-Aliaga, Carmen Rosa (2019)
Childhood anemia is a public health problem in Peru. Physiologically, its main effect is the decrease of oxygen supply to tissues, which can have acute and chronic consequences in the infant, ranging from physical and transient deterioration to severe and permanent deterioration of physical and mental (cognitive) development. The diagnosis of anemia in the infant is not an easy task but by consensus a hemoglobin or hematocrit equal to or lower than the 5th percentile is used as the diagnostic threshold for the age, race and sex of the patient. Hemoglobin levels are usually high (> 14 g/dL) at birth to hemoglobin decrease rapidly, reaching a nadir of ~ 11 g/dL at 6-9 weeks of age due to the "physiological anemia of childhood". The causes of anemia according to the age of presentation. In neonates, immune haemolytic disease, infectious diseases, inherited disorders, delayed umbilical cord clamping, and repeated blood sampling are the most common causes of anemia. In infants from 6 to 24 months of age, anemia is primarily acquired, with iron deficiency anemia (iron-deficiency anemia) being the main cause of anemia at this age. Once the diagnosis of the management of infants with anemia is established, it may require specialized treatment such as managing a primary level, always with rigorous control and monitoring of the signs of severity.